Peran Muhammadiyah dalam Meningkatkan Kesejahteraan Masyarakat - Ahmad Rokhsan Cholis; Milana Abdillah Subarkah (Student Research Journal, 2024)
Muhammadiyah is an Islamic movement, Da'wah Amar Makruf Nahi Munkar, with Islamic beliefs and based on the Al-Qur'an and Sunnah, founded by KH. A. Dahlan on 8 Dzulhijjah 1330 Hijriyah coinciding with 18 November 1912 Miladiyah in Yogyakarta City. The aim of this research is to describe improving community welfare carried out by Muhammadiyah as the leading Islamic organization in Indonesia. This research uses a qualitative methodology with a library approach. The research results show that Muhammadiyah's contribution to improving the welfare of Indonesian society is largely divided into six areas: education, health, economics, social and humanitarian, da'wah and religion, and the development of science and technology. Muhammadiyah has contributed significantly in various fields that have a direct impact on improving the quality of life of the community.